Biologia reprodutiva de Apidoras fuscoguttatus (Siluriformes, Callichthyidae) em riacho de cabeceira da bacia do alto Rio Paraná - Araujo, Renato Braz de [UNESP]; Garutti, Valdener [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2002)
The reproductive biology of Aspidoras fuscoguttatus Nijssen & Isbrücker, 1976 from a stream in São José do Rio Preto, northwestern São Paulo State, Brazil, was monthly investigated in the period of August 1999 to July 2000. Measurements of total length, body weight, gonadal weight and macroscopic assessment of gonadal maturation were performed. Environmental parameters were considered in order to verify associations with the reproductive period. Populational structure showed total length amplitude between 14.2 and 50.8 mm. Pronounced sexual dimorphism was verified. The largest mean values of gonadosomatic relation for females coincided with the rainy season (November to March). Mean length at first sexual maturity was different for males (30.5 mm) and females (37.1 mm). Fecundity varied between 51 and 166 oocytes. Gonadal maturation curve, frequency of maturation stages and size frequency distributions of oocytes in mature ovaries revealed a long reproductive period, suggesting fractional spawning.
Reproductive biology of Aspidoras fuscoguttatus (Siluriformes, Callichthyidae) in a headstream from upper Paraná River basin
Keywords: Biology; Aspidoras; Callichthyidae; Brazil